2022
DOI: 10.1038/s41419-022-05056-5
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circWDR62 promotes temozolomide resistance and malignant progression through regulation of the miR-370-3p/MGMT axis in glioma

Abstract: Exosome-mediated delivery of circular RNAs (circRNAs) is implicated in cancer progression. However, the role of exosomal circRNAs in the chemotherapy resistance of tumours remains poorly understood. Here we identified a novel circRNA, circWDR62. It was found that circWDR62 expression was upregulated in TMZ-resistant glioma cells and TMZ-resistant glioma cell-derived exosomes compared with their controls by using high-throughput microarray analysis and quantitative real-time polymerase chain reaction, and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…The extracted RNAs were reversely transcribed to cDNAs using PrimeScriptTM II Reverse Transcriptase (Takara, Tokyo, Japan). Gene expression was calculated as previously reported [ 34 ]. Primer sequences were illustrated in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…The extracted RNAs were reversely transcribed to cDNAs using PrimeScriptTM II Reverse Transcriptase (Takara, Tokyo, Japan). Gene expression was calculated as previously reported [ 34 ]. Primer sequences were illustrated in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Exosomal circRNAs also play an important role in the development of glioma, including proliferation, immunosuppression, angiogenesis, invasion, migration, and therapeutic resistance. Recent studies have shown that exosomeassociated circRNAs such as circ_104948, circ_0001445, circHIPK3, circWDR62, circMMP1, circ_0012381 play roles in the glioma proliferation process through miRNAs (30,(96)(97)(98)(99)(100). CircNEIL3 promotes glioma progression and exosome-mediated macrophage immunosuppressive polarization via stabilizing IGF2BP3 (101).…”
Section: Liquid Biopsy Analyses Of Exosomal Circrnas In Glioma Gliomamentioning
confidence: 99%
“…Macrophage-derived exosomes circBTG2 overexpression inhibited proliferation and invasion of glioma cells, circMMP1, and circSMARCA5 (circ_0001445) also play roles in the process of invasion and migration (30,98,103,104). Low-dose radiation-induced exosomal circ-METRN plays an oncogenic role in glioblastoma progression and radioresistance through miR-4709-3p/GRB14 pathway; circ_0072083, circWDR62, circ_0042003, circNFIX, circHIPK3, circGLIS3 can resist TMZ in the treatment of glioma (96,97,(105)(106)(107)(108)(109). Figure 2 shows the roles by which exosomal circRNAs may be involved in the development of glioma.…”
Section: Liquid Biopsy Analyses Of Exosomal Circrnas In Glioma Gliomamentioning
confidence: 99%
“…Analogously, Han et al demonstrated that aberrantly expressed exosomal circHIPK3 could accelerate the cancer progression and TMZ resistance by adjusting the miR-421/ZIC5 signaling axis ( Han et al, 2021 ). Geng et al demonstrated the exosome-mediated delivery of circWDR62 in TMZ-resistant glioma cells U251-R. High expression of exosomal circWDR62 can enhance TMZ resistance and malignant progression via regulating the miR-370-3p/MGMT axis ( Geng et al, 2022 ).…”
Section: Exosomal Circrnas In Cancer Therapeutic Resistancementioning
confidence: 99%